«АЛПОМИШ» ДОСТОНИ ЎЗБЕК - ҚОРАҚАЛПОҚ ВЕРСИЯЛАРИДА БОШ ҚАҲРАМОН ШАЖАРАСИ ВА «ҚЎНҒИРОТ» ЭТНОНИМИ ТАЛҚИНИ - Алламбергенова, Н.Г. (SCIENCE and SOCIETY, 2019)
The article is devoted to the analysis of the ethnonym “Kungrad” related to the main character, in different variants of the epos “Alpamish” that is considered to be one of the best works of Uzbek and Karakalpak folklore.